Dekonstrukcja wolnego zawodu w systemie totalitarnym na przykładzie regulacji prawnej wykonywania zawodu rzecznika patentowego w Polsce w okresie stalinowskim - Borowicz, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In Poland before the Second World War, the profession of patent attorney was categorised as one of the so-called liberal professions. Its legal status and rules of practice were compared to the solicitor profession. A patent attorney practiced his profession personally, independently, and autonomously. In order to exercise his profession, he ran an independent patent attorney’s office. In the second half of the 1940s, with the communists taking power in Poland, a radical transformation of the social, political, economic, and legal system of the state along the lines of Stalin’s Soviet Union began. Any social, political, or economic activities characterised by independence and autonomy were thus in axiological contradiction with the ideology of the planned totalitarian state. The Act on the Establishment of the College of Patent Attorneys passed on 20 December 1949 completely abolished the structure of the patent attorney profession as a free profession, exercised in its own name and on its own account. From that moment on, the patent attorney became a civil servant performing their professional activities under strict hierarchical subordination to his superiors. There was no guarantee of their intellectual independence or professional autonomy. The practice of the patent attorney profession was subject to public law. The Patent Attorneys College was in fact another state office. It was organisationally and financially linked to the Patent Office — an administrative body granting legal protection to objects of industrial and commercial property, collecting and making available patent documentation and literature. The president of the Patent Office supervised the Patent Attorneys College. Both the Patent Attorneys College and the Patent Office were supervised by the State Economic Planning Commission. The State Commission for Economic Planning was a kind of super-ministry, tasked with a Soviet-style mission of closely supervising and controlling the entire centralised economy of the Polish state. The chairman of the State Economic Planning Commission also had key powers to influence patent attorneys. It was he who determined the subject of their professional examination, he who appointed a person meeting the statutory requirements to the position of a patent attorney. He could also exempt a candidate for the profession from meeting the requirements as well as appoint the president of the Patent Attorneys College. The Act of 20 December 1949 was repealed with the end of the Stalinist period in Poland. In 1958, the profession of patent attorney was briefly reinstated as a free profession. After that, until the end of the existence of the socialist state called the Polish People’s Republic, patent attorneys performed their profession as employees within the meaning of the labour law. It was not until the fall of communism in Poland that the profession of a patent attorney was re-established as a liberal profession under the provisions of the Act on Patent Attorneys of 9 January 1993.
Keywords: totalitarianism; Stalinism; free profession; patent agent; civil servant